1985
DOI: 10.1515/zna-1985-0104
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave in Condensed Matter Generated by Impulsive Load

Abstract: A shock wave in condensed matter generated by impulsive load ("shock loading") is considered. A self-similar solution of the problem is presented. The media are described by the equation-of-state of the Mie-Grüneisen type. Values of the self-similarity exponent and the profiles of gas-dynamical variables have been calculated. The problem of generation of shock waves by ultra-short laser pulses is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…o 0 8 D B S 2 g 8 n N P G 8 / o j Y y j u 5 p m q A f 8 l E k h 1 J w s q N 2 T 1 l 0 w P v l i l t 1 F 2 K r x s t N B X I 1 + u X P λ/(v s ∆t) = 1 − M 2 2 /M 2 as the dimensionless characteristic frequency, in agreement with (45). Note that different normalization yields λ/(c 2 ∆t) = 1 − M 2 2 .…”
Section: B Transverse Acoustic Modessupporting
confidence: 78%
See 1 more Smart Citation
“…o 0 8 D B S 2 g 8 n N P G 8 / o j Y y j u 5 p m q A f 8 l E k h 1 J w s q N 2 T 1 l 0 w P v l i l t 1 F 2 K r x s t N B X I 1 + u X P λ/(v s ∆t) = 1 − M 2 2 /M 2 as the dimensionless characteristic frequency, in agreement with (45). Note that different normalization yields λ/(c 2 ∆t) = 1 − M 2 2 .…”
Section: B Transverse Acoustic Modessupporting
confidence: 78%
“…Canonical shock problems in gas dynamics, such as Guderley-type converging shock, impulsive-loading, or the popular blast wave problem [43][44][45][46] , can be formulated in absence of temporal and spatial scales through the combination of the inviscid Euler equations and the Rankine-Hugoniot (RH) equations at the shock, provided that additional boundary and initial conditions do not involve spatio-temporal scales. In that case, the possibility of writing a solution in terms of self-similar variables only relies on properties of EoS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, self-similar profiles are displayed in figure 2 for ν = 2 (cylindrical) and ν = 3 (spherical) for three different equations of state that include: ideal gas(a), vdW gas (b) and three-terms equation for aluminum (c), whose constitutive details are provided in Appendix A. Note that the mathematical description for the EoS and the internal energy is not restricted to the reduced Mie-Grüneisen form E( p, ρ) = pf (ρ), where f (ρ) is an arbitrary positive function of density, which is a pre-requisite to construct classic self-similar solutions for blast-wave, impulsive-loading, converging-shock and classic Noh problems (Anisimov & Kravchenko 1985;Sedov 1993;Axford 2000;Giron et al 2020). For example, used a reduced form of the vdW EoS to meet the reduced Mie-Grüneisen form and, therefore, find a self-similar solution for the spherical implosion problems, and Ramsey, Boyd & Burnett (2017) demonstrated that there is no classic Noh solution for spherical and cylindrical geometry with an EoS for which the internal energy is not simply proportional to the pressure.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Self-similar solutions describing the stagnation phase after the shock convergence or the cavity collapse (Guderley 1942;Hunter 1960;Stanyukovich 1960;Lazarus 1981;Zababakhin & Zababakhin 1988;Zel'dovich & Raizer 2002) do not satisfy this requirement. The class of non-ideal EoS permitting these self-similar solutions (Anisimov & Kravchenko 1985;Sedov 1993;Axford 2000;Ramsey et al 2018;Giron, Ramsey & Baty 2020) is narrow, not including most non-ideal EoS of interest. The family of generalized Noh solutions, on the other hand, fits the above requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The Mie-Grüneisen EoS [27,28] p e , 5 ( ) r = G after an approximation, it can be written as [29] constant.…”
Section: Basic Equations and Boundary Conditionsmentioning
confidence: 99%